Total synthesis of the proposed structures of gladiosides I and II. (September 2021) - Hussain, Nazar; Delar, Emmanilo; Piochon, Marianne; Groleau, Marie-Christine; Tebbji, Faiza; Sellam, Adnane; Déziel, Eric; Gauthier, Charles
Abstract: Burkholderia gladioli is a Gram-negative bacterium that biosynthesizes a cocktail of potent antimicrobial compounds, including the antifungal phenolic glycoside sinapigladioside. Herein, we report the total synthesis of the proposed structures of gladiosides I and II, two structurally related phenolic glycosides previously isolated from B. gladioli OR1 cultures. Importantly, the physical and analytical data of the synthetic compounds were in significant discrepancies with the natural products suggesting a misassignment of the originally proposed structures. Furthermore, we have uncovered an acid-catalyzed fragmentation mechanism converting the α, β-unsaturated methyl carbamate-containing gladioside II into the aldehyde-containing gladioside I. Our results lay the foundation for the expeditious synthesis of derivatives of these Burkholderia -derived phenolic glycosides, which would enable to decipher their biological roles and potential pharmacological properties. Graphical abstract: Image 1 Highlights: The total synthesis of the originally proposed structures of gladiosides I and II was achieved. An acid-catalyzed fragmentation mechanism converting gladioside II into gladioside I was uncovered. Physical and analytical data of the synthetic compounds were not in good agreement with the natural compounds. No antimicrobial activities were detected for the synthetic compounds.